Case Report: A Severe SARS-CoV-2 Infection in a Teenager With Angelman Syndrome - Lopes, Alessandra G. D.; Celestino, Camila S. H.; Barros, Tiago T. A.; Fevereiro, Aline G.; Gejer, Debora H.; Oliveira, Fernando M. F.; Brasil, Jamile M.; Bossolan, Rosely M.; Pinto, Gabriela C. C.; Santos, Ana C. E. Z.; Divan, Luis A.; Alves, Ingrid A. B.; et al. (Frontiers in Medicine, 2021)
Teenagers generally present mild to no symptoms of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. In the present report, we present the case of a 14-year-old boy with Angelman syndrome (AS) who presented with severe COVID-19 symptoms. He spent 20 days in the ICU with elevated inflammatory biomarkers (C-reactive protein and D-dimer) and increased peaks of neutrophil-to-lymphocyte ratio, which is uncommon for teenagers diagnosed with COVID-19. Although he showed physiological instability, he was able to produce neutralizing antibodies, suggesting a functional immune response. The literature concerning the immune response to infections in patients with AS is still poor, and to our knowledge, this was the first report of a patient with AS diagnosed with COVID-19. As such, the present study may alert other patients with AS or other rare diseases that they lack a competent immune response and could suffer severe consequences of SARS-CoV-2 infection.